5-Ethyl-5-methyl-4-phenyl-5H-1,2,4-triazol-3(4H)-thione - Tan, Kong Wai; Ng, S.W.; Maah, Mohd Jamil (International Union of Crystallography, 2010)
The five-membered ring of the title compound Delta(1)-1,2,4-triazoline-5-thione, C(11)H(13)N(3)S, is almost planar (r.m.s. deviation = 0.009 angstrom); the phenyl ring is aligned at 84.6 (2)degrees with respect to the five-membered ring. The crystal studied was a racemic twin with an approximate 20% minor twin component. Weak intermolecular C-H center dot center dot center dot N hydrogen bonding is present in the crystal structure.